Similarity relations and exponential of dual-generalized complex matrices - Gurses, Nurten; Senturk, Gulsum Yeliz (OVIDIUS UNIV PRESS, 2023)
In this study, taking into account the fundamental properties of dual-generalized complex (DGC) matrices, various types of similarity relations are introduced considering coneigenvalues/coneigenvectors via di erent conjugates. The exponential version of DGC matrices are identified and then their theoretical characteristic theorems are obtained. Finally, examples for DGC matrix exponential are given.
Keywords: Dual-generalized complex matrices; Fundamental matrix; Eigenvalues and eigenvectors; Similarity; Matrix exponential; CONSIMILARITY; QUATERNIONS; Mathematics